CEREBRUM TUMOUR CLASSIFICATION USING EDGE DETECTION AND CNN - R.Vasuki, Prasath Alias Surendhar S, Sowmiya V (International Journal of Advanced Science and Technology, 2020)
An effective cerebrum cancer discovery technique and a programmed division strategy dependent on Convolution Neural Networks (CNN) and introducing technique for picture division and detecting edges dependent on structural change, which can recognize cancer cells in the mind MRI pictures. Picture arrangement is a significant undertaking in the picture preparing and particularly in the restorative determination field. A slope decided dim dimension morphological method for edge increment and reduction is available. Convolution systems were continued by organic formats and varying multilayer perceptrons are undertaken for preprocessing.